Mucormycosis - Reid, Gail; Lynch, 3rd, Joseph P; Fishbein, Michael C; Clark, Nina M (Seminars in respiratory and critical care medicine, 2020)
Mucormycosis is an infection caused by a group of filamentous molds within the order Mucorales. Infections may result from ingestion of contaminated food, inhalation of spores into the nares or lungs, or inoculation into disrupted skin or wounds. In developed countries, mucormycosis occurs primarily in severely immunocompromised hosts (e.g., those with hematological malignancies, organ transplantation, neutropenia, autoimmune disorders, or other impairments in immunity). Only 6 to 10% of cases occur in subjects with no underlying disease. In contrast, in developing countries, most cases of mucormycosis occur in persons with poorly controlled diabetes mellitus or in immunocompetent subjects following trauma. Mucormycosis exhibits a marked propensity to invade blood vessels, leading to thrombosis, necrosis, and infarction of tissue. Mortality associated with invasive mucormycosis is high (> 30-50%), with 90% mortality associated with disseminated disease. Mortality rates are much lower, though still significant (10-30%), among patients with localized cutaneous disease.The diagnosis of mucormycosis relies upon histopathology and culture. Blood tests are of limited diagnostic value. Even with disseminated disease, blood cultures are usually negative. Mucorales have a distinct histological appearance, with irregular, nonseptate hyphae that branch at right angles. Cultures and/or polymerase chain reaction (PCR) are important to identify the genera.Based on anatomic localization, mucormycosis can be classified as one of six forms: (1) rhino-orbital-cerebral mucormycosis (ROCM), (2) pulmonary, (3) cutaneous, (4) gastrointestinal (GI), (5) disseminated, and (6) mucormycosis of uncommon sites. Among diabetics, ROCM is the most common clinical presentation, whereas lung involvement is uncommon. In contrast, among organ transplant recipients or patients with hematological malignancies (HemeM), pulmonary and disseminated diseases are most common. Mucormycosis can progress rapidly, and delay in initiation of treatment by even a few days markedly worsens outcomes.Due to the rarity of mucormycosis, randomized controlled therapeutic trials have not been performed. Lipid formulations of amphotericin B (LFAB) are the mainstay of therapy, but the newer triazoles, posaconazole (POSA) and isavuconazole (ISAV) (the active component of the prodrug isavuconazonium sulfate), may be effective in patients refractory to or intolerant of LFAB. Early surgical debridement or excision plays an important adjunctive role. Additional studies are required to assess the optimal duration of therapy as well as the specific roles of LFAB and the triazoles in the treatment of mucormycosis.